Robust and well-controlled TiO2–Al2O3 binary nanoarray-integrated ceramic honeycomb for efficient propane combustion. Issue 17 (28th February 2019) - Xiong, Juxia; Luo, Zhu; Yang, Ji; Guo, Yanbing; Piyadasa, Adimali; Wang, Sibo; Hoang, Son; Fang, Yarong; Hu, Siyu; Yang, Weiwei; Deng, Hongtao; Zhang, Lizhi; et al.
Abstract : Well-tuned TiO2 –Al2 O3 binary nanoarrays had been fabricated onto ceramic honeycombs and exhibited excellent robustness and catalytic activity for propane oxidation. Abstract : The catalytic total oxidation of short-chain alkanes released from automobile exhausts is still a big challenge in volatile organic compound (VOC) elimination. The significant degradation of catalytic activity after hydrothermal aging is a widely existing issue. Herein, we report a facile one-pot hydrothermal method to successfully grow TiO2 –Al2 O3 binary nanoarrays on the 3D channel surfaces of ceramic honeycombs. Such a binary nanoarray was heterogeneously integrated on the cordierite honeycomb channel surface with closely separated nanowire arrays of anatase-TiO2 and mesoporous γ-Al2 O3, which exhibited excellent robustness under mechanical vibration and thermal and hydrothermal aging. Moreover, propane conversion with the Pt/TiO2 –Al2 O3 binary nanoarray catalyst rapidly reached 80% at a temperature as low as 224 °C, suggesting that the binary nanoarray catalyst is a promising candidate for practical applications.